Applied soil physical properties, drainage, and irrigation strategies. ([2015]) - McCarty, L. B (Lambert Blanchard), 1958-; Hubbard, Lewis Ray; Quisenberry, Virgil L (Virgil Lee), 1946-
No abstract available